Reading Books Educates Every Student - Adilbaevna, Azatbaeva Nargiza (European Journal of Life Safety and Stability (2660-9630), 2022)
this article discusses the development of reading, which includes the education of students. And also with what ways you can arouse interest in reading books. Despite this, what does reading books lead to, especially in the lower grades? But at the same time, a great concept of reading is given. With this, how can you arouse interest in reading with the help of education? And in what form it is possible to develop their interest or how to support them in everything.